Model Pembelajaran Daring dalam Perkuliahan Pendidikan Lingkungan Hidup di Program Studi Pendidikan Geografi Universitas Tadulako - Samuel Sanda Patampang (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2020)
This research aims to develop an online learning model or Online Learning Model (DLM), as an impelementation to improve the effectiveness of environmental education lectures. Dlm development uses Online Interactive Learning Model (DILM) techniques by utilizing internet-based social media and smartphones as media used in learning. The subject of this research is a student of the Undergraduate program in the education department of IPS Tadulako University which PLH. This study uses mixed approaches or mix methods. Data is collected using questionnaires, questionnaires, and tests. The results of this study showed: 1) Students able to increase the absorption of lecture materials can reach more than 81% compared to using only face-to-face learning models; 2) Can provide a new experience that is more challenging for college students with an online learning model than conventional learning models 3) Environmental education lecturers using online learning models can change the atmosphere of student learning more actively, innovatively, creatively, effectively, and not boring.